Physicochemical analysis, free radical scavenging activity and anti-acetylcholinesterase activity of stingless bee honey - Syafiqah Rahim, Nur; Nurhasnita Wan Hussain, Wan; Mohamad, Sarina; Zainal Ariffian, Zaidah (International Journal of Engineering and Technology, 2018)
Alzheimerâ€™s disease (AD) is characterized by memory loss due to the deficiency of acetylcholine (ACh) concentration in the brain. It can be improved by inhibiting the Acetylcholinesterase (AChE) enzyme through cholinesterase inhibitors. This neurodegenerative disorder also can be caused by neuronal loss through oxidative stress which can be reduced by natural antioxidant. Honey appears to possess high scavenging properties. However, not much study of stingless bee honey focus on AChE inhibition. The objective of this project is to determine the scavenging properties of stingless bee (Heterotrigona itama) honey and its potential as natural AChE inhibitor. Physicochemical analysis of the honey was conducted to test its quality and purity through moisture, ash and pH test. The results show that the purity test is in the standard range of stingless bee honey. Different concentrations of honey were tested for its scavenging properties through DPPH assay. The honey samples were also tested for its AChE inhibitory effect. Results show that the stingless bee honey possesses high scavenging properties at 100% concentration. The inhibition of AChE enzyme showed through the white spot produced on the TLC plate. This finding proves that stingless bee honey able to combat oxidative stress and act as AChE inhibitors.Â Â